Intellectual property rights and the evergreening of pharmaceuticals - Ralf Boscheck (Intereconomics, 2015)
Escalating healthcare expenditures and the need to ensure access to affordable medicine in both emerging and emerged economies are fuelling calls to contain the so-called evergreening practices of drug producers around the world. But such practices are the necessary outcome of a system that responds to market incentives and appears to be already sufficiently controlled by established patentability standards and policies that determine patent term extension. The key issues surrounding current trade disputes lie deeper. This article examines the link between technological advances and intellectual property rights in general and the presumably special case of drug supplies. It focuses on strategies for extending the market exclusivity for pharmaceuticals products and evaluates safeguards against such evergreening.
Keywords: 330; Arzneimittel; Außenhandel; Immaterialgüterrechte; Technischer Fortschritt; Gesundheitskosten; Welt